The M in CITAMS@30 : media sociology - Brienza, Casey; Robinson, Laura (Sociologist); Wellman, Barry; Cotten, Shelia R.; Chen, Wenhong (Studies in media and communications ;, 2018)
Sponsored by the Communication, Information Technologies, and Media Sociology section of the American Sociological Association (CITAMS), this volume is the second of a two-part series that celebrates the section's 30th anniversary. Casey Brienza leads the second of the two volumes - 'The M in CITAMS@30: Media Sociology -'with former CITAMS chairs Laura Robinson, Barry Wellman, Shelia R. Cotten, and Wenhong Chen. Volume 18 continues the discussion begun in Volume 17: 'Networks, Hacking, and Media--CITAMS@30: Now and Then and Tomorrow'. Both volumes highlight some of the best of the vibrant, interdisciplinary scholarship in communication, information technologies and media sociology. Volume 18 develops the field of media sociology vis-à-vis the roles and impacts of the digital and traditional media via rich international case studies that include a broad swath of contexts and cultures. The volume's authors probe the relationships between inequalities and media, as well as offering a scintillating array of scholarship on cultural production and consumption. Assembled together, the work in this volume showcases the value of interdisciplinary scholarship in the sociological study of media, communication, and information technologies. In keeping with the celebration of the thirty-year anniversary, both volumes open with a foreword by past chair Wenhong Chen and close with an afterword by past chair Shelia Cotten.